Pengaruh Gaya Mengajar Guru Terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI Kelas XI di SMAN 1 Sorkam Sumatera Utara - Hasrina Situmeang; Wedra Aprison; Darul Ilmi; Hamdi Abdul Karim (Jurnal Budi Pekerti Agama Islam, 2024)
This study aims to determine the effect of teaching style on student learning outcomes in PAI subjects at SMAN 1 Sorkam North Sumatra. The type of research used is quantitative approach research which is correlation. In collecting data, the researcher used documents for student learning outcomes and a closed questionnaire for the teacher's teaching style with a statement of 20 statement items. The population in this study was the entire class XI SMAN 1 Sorkam North Sumatra which amounted to 121 people while the sample used in this study was 75 respondents. then the conclusion that can be put forward in this study there is an influence of the teacher's teaching style on student learning outcomes in PAI subjects SMAN 1 Sorkam North Sumatra.